Unmute the Organization Through Serious Play - Heldal, Frode; Dehlin, Erlend; Oddane, Torild Alise (Frontiers in Psychology, 2021)
In this article, we sketch up an action research process designed to give voice to those who traditionally have not had a voice in organisations. In particular, the research process was structured around ‘serious play’ and designed as a talk show, where researchers played parts, including a talk show host, and where questions pertaining to organisational life were discussed in depth. The structure of the discussion was construed based on reflective teams, i.e. two actors performing a dialogue (talk show host and guest) and a silent group (audience) as listeners. The key research question concerns in what ways such an action research process is replicable? Applying a critical lens, we argue that even if strong claims of replicability are not met, as in being able to reproduce results and/or generalize them, this is outside the point. Rather, as we set out to apply a qualitative research design to achieve cogenerative learning effects, we advance an understanding of replicability-as-recoverability. This entails giving explicit grounds for our epistemic anchoring in critical realism and sketching out a research design which is sufficiently clear and transparent to undergo critical scrutiny.